The Effect of Environmental Assurance Statements and Digital Reporting Platforms on the Relevance of Financial Information in Agricultural Sector Issuers - Sarie, Fatma; Novitasari, Salwa Aulia; Arini, Rani Eka (West Science Interdisciplinary Studies, 2025)
This study examines the effect of environmental assurance statements and digital reporting platforms on the relevance of financial information in agricultural sector issuers in Indonesia. The increasing demand for transparent, credible, and timely financial reporting that incorporates sustainability issues motivated this research. Using a quantitative approach, data were collected from 160 respondents through a structured questionnaire with a five-point Likert scale. The data were analyzed using SPSS version 25, employing validity and reliability tests, classical assumption tests, regression analysis, and hypothesis testing. The results reveal that environmental assurance statements significantly improve the relevance of financial information by increasing the credibility and reliability of disclosures. Similarly, digital reporting platforms significantly enhance relevance by improving accessibility, timeliness, and transparency of financial data. Simultaneous testing further confirms that both variables jointly strengthen the relevance of financial reporting. These findings contribute to the literature on financial reporting quality and provide practical implications for issuers, regulators, and investors in the agricultural sector, emphasizing the integration of sustainability assurance and digital transformation as strategic drivers of decision-useful financial information.